Multi-method dating constrains the diversification of early eukaryotes in the Proterozoic Mbuji-Mayi Supergroup of the D.R.Congo and the geological evolution of the Congo Basin. (February 2023) - François, C.; Baludikay, B.K.; Debaille, V.; Birck, J.L.; Limmois, D.; Jourdan, F.; Baudet, D.; Paquette, J.L.; Delvaux, D.; Javaux, E.J.
Abstract: We present a petrological and geochronological study of the Proterozoic Mbuji-Mayi sedimentary Supergroup (Sankuru-Mbuji-Mayi-Lomami-Lovoy basin, Democratic Republic of the Congo) and of the overlying subvolcanic doleritic rocks. Dating this Supergroup in Central Africa is crucial to reconstruct the geological history and evolution of the Congo Basin and because it contains a large diversity of organic-walled microfossils including early eukaryotes. For this study, we use the Re–Os dating method on kerogen from shales from the top of the lower Group BI (which contains the microfossils) and Ar–Ar, Sm–Nd and U–Pb methods on the dolerites emplaced near the top of the succession, defining the end of the sedimentation in the basin. The 187 Re/ 187 Os dating yield an age of 1041 ± 58 Ma. For the dolerites, 40 Ar/ 39 Ar dating provide a similar minimum age from 1006 ± 13 to 1009 ± 32 Ma in the whole basin. 147 Sm/ 143 Nd dating confirms a less precise but overlapping age of 926 ± 170 Ma for sample from the Western part of the basin. Some 40 Ar/ 39 Ar dating and U–Pb dating provide also inherited Archean ages. The weighted average age for igneous samples from the basin is 1006 ± 12 Ma. This confirms that the upper Group BII was deposited from 1030 to 1040 to 1006 Ma, consistent with previous U–Pb dating on diagenetic minerals and with biostratigraphy. This new dating provides constraints on the late Mesoproterozoic – early Neoproterozoic diversification of early eukaryotes in Central Africa. We also compare the petrology, geochemistry and geochronology of dolerites from different locations of the basin. Our new data evidence a common origin for all the subvolcanic rocks, emplaced in an intraplate setting and intruding the Archean basement, and indirectly date the end of the extensional stage that initiated the development of the Congo Basin. Highlights: Dating on different dolerites from the SMLL basin provides a similar age around 1.0 Ga. This study furnishes informations on the Congo Basin geodynamics. These new ages provide constraints on the diversification of eukaryotes in Central Africa.